THE EFFECT OF JIGSAW TECHNIQUE ON READING COMPREHENSION OF NARRATIVE TEXT OF THE SECOND YEAR STUDENTS OF MTs.PP.SYAFA’ATURRASUL TELUK KUANTAN - Ummah, Rhadiatul; Azhar, Fadly; ', Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This pre-experimental research was aimed at to find out whether there is a significant effect of Jigsaw Technique on reading comprehension of narrative text of the second year students of MTs.PP.Syafa’aturrasul Teluk Kuantan. Thus, the problem to be discussed was: Is there any significant effect of Jigsaw Technique on reading comprehension of narrative text of the second year students of MTs.PP.Syafa’aturrasul Teluk Kuantan. The design of the research was one group pretest-posttest design. Cluster sampling technique was used to select one class to become the sample. 30 students of class VIII-C at the second semester of academic year 2016/2017 were chosen as the sample. The results of the data analysis showed that the mean score of post-test was higher than pre-test. The result also showed that the value of t-test was higher than t-table at the significance level 5%. It could be concluded that there was a significant effect of jigsaw technique on reading comprehension of narrative text of the second year students of MTs.PP.Syafa’aturrasul Teluk Kuantan.Keywords: Jigsaw Technique, Reading Comprehension, Narrative Texts.